Evidence of morphological variation in an isolated refuge population of the Sonoyta pupfish (Cyprinodon eremus) (Teleostei: Cyprinodontidae) - Alexsandre Gutiérrez-Barragán (Biotecnia, 2024)
The Sonoyta pupfish (Cyprinodon eremus) is an endangered species endemic to the Sonoyta River basin, in northwestern México and southwestern United States. To assist the conservation efforts for this species in México, a refuge population was established in an artificial pond in 1988 at Centro Ecológico de Sonora in Hermosillo, Sonora by translocating individuals from the Sonoyta River population. We used multivariate morphometric methods to delineate body shape variations in the refuge population after 29 years of isolation, in comparison with wild individuals collected from the same sample. Significant variations were observed in body shape between refuge and wild populations. These variations are potentially attributable to different environmental conditions that influenced the refuge and wild populations.